Paediatric end-stage renal disease in a tertiary hospital in South West Nigeria (2014)
Background: Children and adolescents with end-stage renal disease (ESRD) in sub-Saharan Africa may have the worst outcomes globally. Barriers to management include late presentation, poor socioeconomic conditions, absence of medical insurance, limited diagnostic facilities and non-availability of chronic renal replacement therapy (RRT). Our study was to determine the incidence, aetiology, management and outcomes of paediatric ESRD in a tertiary hospital in Nigeria. Methods: A retrospective case review of paediatric ESRD at the University College Hospital Ibadan, Nigeria, over 8 years, from January 2005 to December 2012. Results: 53 patients (56.6% male), median age 11 (inter quartile range 8.5-12) years were studied. Mean annual incidence of ESRD in Ibadan for children aged 14 years and below was 4 per million age related population (PMARP) while for those aged 5-14 years it was 6.0 PMARP. Glomerulonephritis was the cause in 41 (77.4%) patients amongst whom, 29 had chronic glomerulonephritis and 12 had nephrotic syndrome. Congenital anomalies of the kidneys and urinary tract (CAKUT) accounted for 11 (21.2%) cases, posterior urethral valves being the most common. Acute haemodialysis, acute peritoneal dialysis or a combination of these were performed in 33 (62.3%), 6 (11.3%) and 4 (7.5%) patients respectively. Median survival was 47 days and in-hospital mortality was 59%. Conclusions: Incidence of paediatric ESRD in Ibadan is higher than previous reports from sub-Saharan Africa. Glomerulonephritis, and then CAKUT are the most common causes. Mortality is high, primarily due to lack of resources. Preventive nephrology and chronic RRT programmes are urgently needed.